Knowledge Mapping Analysis of Research on Pregnancy-Related Pelvic Girdle Pain (PPGP) from 2002 to 2022 Using Bibliometrics - Xu, Linli; Li, Yuanchao; He, Yanan; Chen, Mengtong; Zhang, Yuting; Liu, Chunlong; Zhang, Li (Journal of pain research, 2024)
Pregnancy-related Pelvic Girdle Pain (PPGP) is a prevalent condition characterized by various physiological and pathological processes in the female body. The objective of this study is to offer a comprehensive understanding of the current research landscape, key areas of interest, and potential future directions in the field of PPGP. Using Web of Science, we explored PPGP literature from 2002 to 2022. VOSviewer and CiteSpace facilitated a quantitative analysis, revealing co-authorship patterns, co-occurring themes, citations, and co-citations. We identified, peaking at 99 publications in 2021. The United States led with 138 publications and the highest citation count (3160). The Karolinska Institute boasted the highest tally of publications (n = 21). Regarding the volume of publications, the esteemed journal of BMC Pregnancy and Childbirth attained the foremost position. Notably, Gutke, Annelie emerged as the most prolific and highly cited author. The analysis of keyword co-occurrence and co-citation clustering unveiled an intricate tapestry of PPGP studies, spanning various domains including risk factors, mechanistic intricacies, diagnostic benchmark, treatment modalities, and far-reaching ramifications on one's quality of life. Research endeavors exploring PPGP have unveiled an enduring trajectory of growth in contemporary times. The existing body of research primarily focuses on delving into the intricate interplay of epidemiological factors and the profound implications of interventions encompassing physical therapy, exercise protocols, and diverse modes of pain management within the domain of PPGP. Multidisciplinary integration encapsulates a prevailing trajectory of progress within this domain, while the focal point of future inquiries into PPGP may revolve around subjects pertaining to standardized outcome reporting.